Empowering Student Larvae Monitors (Simantik) as a Dengue Fever Prevention Strategy in Elementary Schools, Binanga Public Health Center, Mamuju. - Agus Erwin Ashari; Zrimurti Mappau (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem in Indonesia, including in Mamuju Regency, West Sulawesi, where cases have doubled in recent years. This community service activity aimed to empower elementary school students as larval monitors (Simantik) to prevent the spread of DHF in the working area of the Binanga Community Health Center (Puskesmas). The activity was conducted from March to October 2023 at three elementary schools: SD Inpres Binanga I, II, and III, involving 170 fifth-grade students. The methods included health counseling on DHF, simulation and practice of larval monitoring, distribution of posters, installation of banners, and formation of Simantik groups at each school. Pre-test and post-test questionnaires were administered to evaluate changes in students' knowledge. The results showed a significant increase in students' knowledge about DHF prevention after the intervention. The Simantik program effectively engaged students in independently monitoring mosquito larvae in their school and home environments. This activity demonstrated that school-based larval monitoring empowerment programs have the potential to reduce DHF cases at the community level. The formation of Simantik groups is recommended as a sustainable strategy for dengue prevention in primary schools.